Effective verbal communication - Hayes, Denis, 1949- (London : Hodder and Stoughton, 1998)
The power of the spoken word. Clarity of speech. Speaking and listening. Classroom talk. Teaching and learning. Motivation and class control. Speaking to adults.
Keywords: Teaching; Oral communication; Teaching; Teacher effectiveness; Oral communication